2015
DOI: 10.1016/j.biopsych.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Neuroanatomical Correlates of Fear Expression in Prefrontal-Amygdala Circuits

Abstract: Background The neural projections from the infralimbic region of the prefrontal cortex (IL) to the amygdala are important for the maintenance of conditioned fear extinction. Neurons in this pathway exhibit a unique pattern of structural plasticity that is sex-dependent, but the relationship between the morphological characteristics of these neurons and successful extinction in males and females is unknown. Methods Using classic cued fear conditioning and extinction paradigm in large cohorts of male and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
113
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 40 publications
18
113
3
2
Order By: Relevance
“…The trend for decreased preference in SKF 81297-treated mice during the Post-Extinction test led us to examine whether initial preference influenced the effect of SKF 81297 on extinction (Weber et al, 2007;Bernardi and Lattal, 2012;Gruene et al, 2015). To assess high or low cocaine preference, a median preference value was calculated from all subjects (48 animals) during the Pre-Ext Test, which occurred prior to delivery of SKF 81297.…”
Section: Post-session Skf 81297 Does Not Generate Cpp and Enhances Exmentioning
confidence: 99%
“…The trend for decreased preference in SKF 81297-treated mice during the Post-Extinction test led us to examine whether initial preference influenced the effect of SKF 81297 on extinction (Weber et al, 2007;Bernardi and Lattal, 2012;Gruene et al, 2015). To assess high or low cocaine preference, a median preference value was calculated from all subjects (48 animals) during the Pre-Ext Test, which occurred prior to delivery of SKF 81297.…”
Section: Post-session Skf 81297 Does Not Generate Cpp and Enhances Exmentioning
confidence: 99%
“…Recent behavioral work on male and female rats undergoing fear conditioning and extinction involving, respectively, the prelimbic and infralimbic PFC (Santini et al, 2008) has revealed sex differences based upon individual differences in efficacy of extinction (poor extinction, HF; good extinction, LF) that were evident in both males and females (Gruene et al, 2014). Despite no overall sex differences in freezing behavior, the HF/LF phenotypes emerged in males during extinction, but in females it emerged during fear conditioning, which does not involve infralimbic-BLA neurons.…”
Section: Females Respond Differently To Chronic Stressmentioning
confidence: 99%
“…A handful of studies have directly compared animals of both sexes on tests of cued and contextual fear conditioning. Some of these reports have shown that while males and females exhibit equivalent levels of fear conditioning to discrete cues (Maren et al 1994;Baran et al 2009;Milad et al 2009a;Barker and Galea 2010;Gruene et al 2015a;Fenton et al 2016), males often show evidence of better contextual conditioning (Maren et al 1994;Chang et al 2009;Barker and Galea 2010). Other studies have tested for sex differences in fear extinction learning, a form of learning through which animals learn to inhibit responding to cues that once signaled an aversive event.…”
mentioning
confidence: 99%
“…Over the last several years, the study of fear extinction has received considerable attention (Milad and Quirk 2012) due in part to the fact that humans with PTSD display impaired extinction (Milad et al 2009b;Norrholm et al 2011). Recent findings in rodents are mixed with regard to sex differences in fear extinction with several studies reporting no difference between males and females (Milad et al 2009a;Rey et al 2014;Gruene et al 2015a), while others have found that females show weaker fear extinction (Baran et al 2009(Baran et al , 2010Matsuda et al 2015;Fenton et al 2016). Moreover, other studies have found that the retention of extinction learning in female rats varies depending on estrus stage such that rats exposed to extinction training while in proestrus show better retention of extinction (Milad et al 2009a;Rey et al 2014).…”
mentioning
confidence: 99%